Thomas Jefferson: Westward the Course of Empire - Kaplan, Lawrence S. (Rowman & Littlefield Publishers, 1998)
This biography of one of America's greatest political figures focuses on Thomas Jefferson's role as a maker of foreign policy. Although he was not the sole formulator of American diplomacy, Jefferson's voice was the most pervasive in the first generation of the republic's history. This text explores how the concept of the United States' westward expansion worked as the moving force in forming Jefferson's judgments and actions in foreign relations. Although much has been written about Jefferson, this volume is one of the few that explores the full range of his positions on foreign relations. Readable and authoritative, Thomas Jefferson: Westward the Course of Empire offers new insight into the man who shaped American foreign policy.